Carbon Management and Wealth Maximization of Listed Financial Services Firms in Nigeria - Adekanmi, Aderemi Daniel; Aduwo, Ayomikun Elizabeth; Alabi, Samuel Adebayo; Falusi, Iyiola Emmanuel (The Journal of Accounting and Management, 2024)
This study investigates the effect of carbon management strategies on wealth maximization of listed financial services firms in Nigeria. Utilizing panel secondary data from eight selected firms over the period 2014-2023, sourced from annual financial statements, the research explores variables such as carbon emissions intensity (CMI), renewable energy adoption (REA), and carbon pricing implementation (CPI). Results indicate a significant positive impact of these carbon management practices on wealth maximization. Specifically, increases in carbon emissions intensity, adoption of renewable energy sources, and implementation of carbon pricing mechanisms correlate with higher wealth maximization for the studied firms. The study underscores the importance of integrating carbon management into financial decision-making processes and offers recommendations for policymakers to incentivize sustainable practices within the financial sector. These findings contribute to both academic understanding and practical implications for enhancing financial performance while mitigating environmental impact in emerging markets like Nigeria.